Serum ferritin concentration as an index of storage iron in rheumatoid arthritis - Bentley, D. P. (1974)
Serum ferritin concentration has been compared with semi-quantitative histochemical estimates of bone marrow iron deposits in 60 anaemic patients with rheumatoid arthritis. There was considerable variation in the visual assessment of iron stores made by different observers. Serum ferritin appears to be a particularly sensitive index of iron status when stores are low. The best means of detecting iron deficiency in rheumatoid arthritis are discussed.